ZFAS1 functions as an oncogenic long non-coding RNA in bladder cancer - Yang, Haifan (Biosci Rep, 2018)
Long non-coding RNA (lncRNA) ZFAS1 (zinc finger antisense 1) has been suggested to have an oncogenic role in the tumorigenesis of human malignant tumors. However, the expression status and biological function of ZFAS1 in bladder cancer is still unknown. Thus, the purpose of the present study is to explore the clinical value of ZFAS1 in bladder cancer patients, and the biological function of ZFAS1 in bladder cancer cell. In the present study, we found ZFAS1 expression was increased in bladder cancer tissues compared with paired adjacent normal tissues through analyzing the Cancer Genome Atlas (TCGA) database. Furthermore, we confirmed that levels of ZFAS1 expression were elevated in bladder cancer tissues and cell lines compared with normal bladder tissues and normal uroepithelium cell line, respectively. Then, we observed that the expression level of ZFAS1 was positively associated with clinical stag, muscularis invasion, lymph node metastasis, and distant metastasis in bladder cancer patients. The experiments in vitro suggested that knockdown of ZFAS1 repressed bladder cancer cell proliferation via up-regulating KLF2 and NKD2 expression, and inhibited cell migration and invasion via down-regulating ZEB1 and ZEB2 expression. In conclusion, ZFAS1 is overexpressed in bladder cancer, and functions as an oncogenic lncRNA in regulating bladder cancer cell proliferation, migration, and invasion.